COVID-19: the impact of a global crisis on sustainable development research - Leal Filho, Walter; Azul, Anabela Marisa; Wall, Tony; Vasconcelos, Claudio R. P.; Salvia, Amanda Lange; do Paco, Arminda; Shulla, Kalterina; Levesque, Vanessa; Doni, Federica; Alvarez-Castanon, Lorena; Mac-Lean Bravo, Claudia Alejandra; Avila, Lucas Veiga; et al. (My University, 2021)
The crisis caused by COVID-19 has affected research in a variety of ways. As far as research on sustainable development is concerned, the lockdown has significantly disrupted the usual communication channels and, among other things, has led to the cancellation of meetings and long-planned events. It has also led to delay in the delivery of research projects. There is a gap in the literature in regards to how a global crisis influences sustainability research. Therefore, this ground-breaking paper undertakes an analysis of the extent to which COVID-19 as a whole, and the lockdown in particular, has influenced sustainability research, and it outlines the solutions pursued by researchers around the world to overcome the many challenges they have experienced. This paper also outlines some measures that may be implemented in the future to take more advantage of existing technologies that support research on sustainable development.
Keywords: covid-19; sustainability; research; crisis